Global Impact and Intersectionality: A Comprehensive Analysis of the CRPD's Implementation and the Future of Disability Rights in International Law - Suleiman, Nashwan Mohammed; Majeed, Ahmed Saad Abdu Al Jabar; Zuhair, Mohammed; Jasim, Bushra Abd Al-Lattif; Turchyn, Maryna (Journal of Ecohumanism, 2024)
Introduction: The Convention on the Rights of Persons with Disabilities (CRPD), a crucial convention in international law, has resulted in substantial progress in disability rights worldwide after its endorsement by the United Nations in 2006. Nonetheless, applying the CRPD in real-world scenarios and examining how disability intersects with international human rights legislation are intricate subjects that need thorough investigation. Objective: The primary objective of this study is to comprehensively examine the complexities and consequences of the CRPD, with a particular focus on its worldwide influence, practical application in diverse national contexts, and its interconnectedness with other dimensions of identity and developing global challenges. Methods: This lengthy study compares legislative frameworks and CRPD implementation in various nations. It examines disability intersectionality in international human rights legislation using theme analysis. Trend analysis also considers how growing global challenges may affect disability rights. Results: The article found that nations implement differently, showing the numerous difficulties disabled people confront, especially when considering intersectionality. Global problems provide both challenges and opportunities for disability rights under international law. Conclusion. The study emphasizes the essential significance of CRPD while drawing attention to critical areas that need more investigation and enhancement. Specifically, these areas include the practical application of the CRPD, the consideration of intersectionality, and the ability to adapt to changing global circumstances. The argument supports the adoption of a comprehensive, inclusive, and flexible strategy within the realm of international law to protect and promote disability rights on a worldwide scale effectively.